THE RELATION BETWEEN GENDER AND DIFFERENCES IN EMOTIONAL INTELLIGENCE OF FEMALE MANAGERS IN MODERN RURAL TOURISM - Čolović, Milica; Nikić, Gordana; Stamatović, Milan (Economics of Agriculture, 2021)
The main goal of this research is to examine the relation between gender and differences in affective attachment, emotional intelligence and self-esteem among students population. The scales for self-assessment of emotional intelligence, affective attachment and self-esteem were used in the current research. The sample consisted of 231 respondents, students of tourism and hospitality management, 71 males and 160 females. Considering that our sample is not representative, because there is a large disproportion in the number of male and female respondents, and that distribution of scores on measured variables deviates from normal, we used nonparametric techniques: Mann–Whitney U test and Kruskal-Walis one way analysis of variance. The results show that female students have more pronounced emotional intelligence in the domain of perceiving and understanding emotions, as well as a better ability to regulate and manage emotions compared to male respondents, while the measured scores at scale of affective attachment and self-esteem did not show statistically significant differences between gender. On further, female managers in our research see the development of rural tourism as their business opportunity.